Zakat and Waqf Model in Reducing Poverty among Vulnerable Groups During the Pandemic in Nigeria - Muhammad, Adamu Abubakar; Fajri, Mohammad Zen Nasrudin; Idriss, Ibrahim Dahiru; Wani, Athar Shahbaz (Universitas Darussalam Gontor, 2024)
The crisis of COVID-19 pandemic has already crushed and affected almost everyone in the world. In terms of economy, the vulnerable group was the most affected group in the society as many of them lose their jobs and thus poverty rate rose. Poverty is a worldwide spread problem that results pains and loss of confidence to many people in the world where vulnerable citizens of Bauchi state-Nigeria are not excluded. The menace of poverty during COVID-19 pandemic can be alleviated through proper Zakat and Waqf administrations. This study explores the possible uses of Zakat and Waqf as financing tools for poverty alleviation during COVID-19 pandemic on the vulnerable in the society. The qualitative approach is adopted which includes review of related literatures and interview with relevant bodies and individuals. The findings of the study reveals that Zakat and Waqf as an Islamic finance models have relevant potential to fight any contemporary crisis and pandemic in respect of geographical location, era, people or religion. Zakat and Waqf if properly organized, maintained, collected, well managed and truthfully distributed to the people concerned can help in fighting the adverse effect of COVID-19 pandemic and alleviate poverty among the vulnerable in Bauchi state Nigeria.